Analysis of Star, Tree and Mesh Optical Network Topologies for successive distance between nodes Using Optimized Raman-EDFA Hybrid Optical Amplifier (International Journal of Engineering and Computer Science, 2015)
Analysis of the performance of star, tree and mesh topologies is made for successive distance between the nodes at the bit rate of 15 Gbps . The number of users supported at different distances is calculated in terms of Quality Factor and BER for the input signal power of -40dBm. An optimized Hybrid Raman-EDFA amplifier is used for post amplificion. Mach-Zehnder modulator at extinction ratio of 30dB with symmetry factor of -1 is used for the modulation of signals. The spacing between the channels is taken as 0.1 THz with the line width of 1 MHz. It is observed that Star topology is capable to support more users than other topologies for a distance of 6Km in terms of quality factor and BER.